Bridging the Partisan Divide? Exploring Ambivalence and Information Seeking Over Time in the 2012 U.S. Presidential Election. Issue 3 (4th May 2017) - Hmielowski, Jay D.; Beam, Michael A.; Hutchens, Myiah J.
Abstract : Research has shown that holding conflicted attitudes (ambivalence) about political decisions may lead people to act as ideal citizens. One example of this normatively ideal behavior is seen in research linking ambivalence to information seeking. To expand on this line of inquiry, this study examines the over-time relationship between ambivalence and information seeking. We use three-wave panel data collected during the 2012 election to determine whether over-time relationships exist between these variables and test the causal direction of these relationships. We find that use of counterattitudinal information increases ambivalence, which leads people to seek out more counterattitudinal information. We also find that use of pro-attitudinal media decreases levels of ambivalence.